Molecular identification of sparganum of Spirometra mansoni isolated from the abdominal cavity of a domestic cat in Vietnam - NGUYEN, Yen Thi Hoang; NGUYEN, Lan Anh Thi; DONG, Hieu VAN; DUONG, Hieu Duc; YOSHIDA, Ayako (Journal of Veterinary Medical Science, 2024)
Cats normally play a role of the definitive host in which the plerocercoid (sparganum), the second larval form of Spirometra spp., develops into an adult in the intestines. However, some cases of cats with visceral or subcutaneous sparganosis were sporadically reported worldwide. We herein documented the discovery of a sparganum in abdominal cavity of a domestic cat during a surgery of dystocia. The larva was molecularly identified as Spirometra mansoni, belonging to Type I, that was recently misidentified to be S. erinaceieuropaei in several Asian countries. This is the first report for sparganum of S. mansoni in the cat. The future study is necessary to provide further insights into the species of Spirometra causing sparganosis and spirometrosis in humans and other animals.